Applications of calcium and boron increase yields of Italian tomato hybrids (Solanum lycopersicum) in two growing seasons - Zamban, Débora T.; Prochnow, Daiane; Caron, Braulio O.; Turchetto, Mônica; Fontana, Daniele Cristina; Schmidt, Denise (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
The objective of this study was to evaluate the effect of boron soil treatments and the frequency of calcium applications on the flowering, agronomic performance, and incidence of blossom end rot in Italian tomato hybrids grown in conventional systems during two growing seasons. Two experiments were carried out in the experimental area of the Federal University of Santa Maria, Frederico Westphalen campus (Brazil) during 2012 and 2013. A randomized block experiment design was used in a 2×2×3×3 factorial scheme with two hybrids (San Vito and Netuno) in two growing seasons (Spring-Summer and Summer-Fall), three boron doses (0.0, 2.0, or 4.0 g/hole), and three frequencies of calcium application (absence of application, weekly, or biweekly application) with four replicates. The seedlings were transplanted on September 4, 2012 for the Spring-Summer growing season and on January 26, 2013 for the Summer-Fall growing season. The Netuno hybrid was more productive in comparison to the San Vito hybrid, but more susceptible to blossom end rot. Both growing seasons can be recommended for Italian tomato production in Rio Grande do Sul although the Spring-Summer growing season was more productive than the Summer-Fall growing season. The biweekly application frequency of 0.6% CaCl2 was the best option for fertilizer management, resulting in higher yields and a lower number of fruits with an incidence of blossom end rot. The increment of the boron dose defined the higher number of fruits per plant and yield increase.